The Portuguese Community at the Periphery: A Minority Report on the Portuguese Quest for the Bumiputera Status - Gerard Fernandis (Kajian Malaysia, 2003)
The first time and the first opportunity that the Portuguese Eurasian Community made a statement publicly about their status was in the Constitutional Proposals for Malaya in 1947 whereby the Malayan Eurasian Union stated: The Eurasians being the sons of the soil (Bumiputra)r in Malaya have no other country which we can regard as our homeland. Our forefathers have always claimed that as a fact and the present generation and our further generations will always claim Malaya as our Mother Country' To substantiate our claim we might mention that it would not be practical to banish a Eurasian from Malaya if he ever commits a crime calling for such a penalty.